1997
DOI: 10.1103/physrevd.55.3552
|View full text |Cite
|
Sign up to set email alerts
|

Optical approach for the thermal partition function of photons

Abstract: The optical manifold method to compute the one-loop effective action in a static space-time is extended from the massless scalar field to the Maxwell field in any Feynman-like covariant gauge. The method is applied to the case of the Rindler space obtaining the same results as the point-splitting procedure. The result is free from Kabat's surface terms which instead affect the -function or heat-kernel approaches working directly in the static manifold containing conical singularities. The relation between the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…In this way we have shown that the first quantum correction to the black hole entropy due to the electromagnetic field, which we have computed by using the semi-classical approximation, is exactly twice the one which one has for a scalar field. This means that the anomalous contributions, which one has for the Rindler case [25][26][27], are not present in this context.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this way we have shown that the first quantum correction to the black hole entropy due to the electromagnetic field, which we have computed by using the semi-classical approximation, is exactly twice the one which one has for a scalar field. This means that the anomalous contributions, which one has for the Rindler case [25][26][27], are not present in this context.…”
Section: Resultsmentioning
confidence: 99%
“…In any case, as suggested in Ref. [27], such terms are non physical and have to be discharged. All results of this section have a good limit for Q → 0 and so they are valid also for the Schwarzschild black hole, with the simple substitution r h = 2M , r − = 0.…”
Section: Electromagnetic Fields In Schwarzschild and Reissner-nordstrmentioning
confidence: 99%
See 1 more Smart Citation
“…Formal proofs concerning the effective Lagrangian in more general cases can be found in [BD82]. Recently, the local approaches have proven to give untrivial results if compared with global approaches based on heat kernel procedures [ZCV96,IM96,MI97] whenever the manifold contains singularities physically relevant. Just as conjectured by Wald, methods based on local ζ function have been found out which are able to regularize and renormalize the one-loop averaged squared field fluctuations [IM98] and the one-loop stress tensor [Mo97a] directly (anyhow, a first remarkable formal attempt still appeared in [Ha77]).…”
Section: Introductionmentioning
confidence: 99%
“…Since the appearance of these papers, a large use of these techniques has been done by physicists, in particular, to compute one-loop partition functions within semiclassical approaches to the Quantum Gravity and also concerning other related areas [BCVZ96,EORBZ94,El95,Ca90]. After the fundamental works cited above, many efforts have been spent in studying the black hole entropy and related problems by these approaches (for recent results see [CKVZ,MI97,IM96]). The local ζ-function approach differs from integrated ζ function approaches because the former defines quantities which may depend on the point on the manifold and thus can be compared with analogue regularized and renormalized quantities produced from different more usual local approaches as the point-splitting one [BD82,Fu91].…”
Section: Introductionmentioning
confidence: 99%